Structure‐Dependent Electronic Nature of Star‐Shaped Oligothiophenes, Probed by Ensemble and Single‐Molecule Spectroscopy. Issue 29 (4th June 2013) - Chung, Heejae; Narita, Tomoyuki; Yang, Jaesung; Kim, Pyosang; Takase, Masayoshi; Iyoda, Masahiko; Kim, Dongho
Abstract We have investigated the photophysical properties of star‐shaped oligothiophenes with three terthiophene arms (meta to each other, S3) or six terthiophene arms (ortho‐, meta‐, and para‐arranged, S6) connected to an ethynylbenzene core to elucidate the relationship between their molecular structure and electronic properties by using a combination of ensemble and single‐molecule spectroscopic techniques. We postulate two different conformations for molecules S3 and S6 on the basis of the X‐ray structure of hexakis(5‐hexyl‐2‐thienlyethynyl)benzene and suggest the coexistence of these conformers by using spectroscopic methods. From the steady‐state spectroscopic data of compound S6, we show that the exciton is delocalized over the core structure, but that the meta‐linkage in compound S3 prevents the electronic communication between the arms. However, in single‐molecule spectroscopic measurements, we observed that some molecules of compound S3 showed long fluorescence lifetimes (about 1.4 ns) in the fluorescence‐intensity trajectories, which indicated that π electrons were delocalized along the meta linker. Based on these observations, we suggest that the delocalized exciton is intensely sensitive towards the dihedral angle between the core and the adjacent thiophene ring, as well as to the substituted position of the terthiophene arms. Our results highlight that the fluorescence lifetimes of compounds S3 and S6 are strongly correlated with the spatial location of their excitons, which is mainly affected by their conformation, that is, whether the innermost thiophene rings are facing each other or not. More interestingly, we observed that the difference between the degrees of ring‐torsional flexibility of compounds S3 and S6 results in their sharply contrasting fluorescence properties, such as a change in fluorescence intensity as a function of temperature.